Imaginários juvenis: cinema, recepção, mediações e consumo cultural - Nóbrega, Thais Zonta de (2015)
This investigation have as principal object the reflection through filmic narratives and receivers narratives about the imaginary of today's youth, the 2010s, comparing it with readings of other times, for example, the 1960s and the 1980s, that is, comparing different generational moments. The questions that guide the research are: how movies Somos tão Jovens (2011) and Confissões de Adolescentes (2013) conceive youth? Moreover, how the young receivers equate their own narratives based on film and on their experiences of everyday life? The methodology consists of the study of cinematographic reception, of reading the filmic narratives, cinema as mediation, and of mediations situational, media and generational. The generational mediation sews the dissertation as a whole, especially in view of the comparison between the two filmic narratives analyzed, Somos tão jovens and Confissões de Adolescentes, which are in different generational times. Briefly, the theoretical and methodological foundations that inspired this dissertation consist of reflections on mass culture and imaginary (Edgar Morin), of Latin-Americans Cultural Studies, of the great methodological key Jesús Martín-Barbero, mediation, and of the British Cultural Studies, especially Raymond Williams, emphasizing the reading of uses, and putting in relief the appropriation forms, contemplated in the study of reception. The dissertation divides into three chapters. The first present a general picture of Brazilian cinema and youth debate; more than that, about how the youth has been designed by cinema in recent decades. The second chapter will cover some of the pictures of youth made possible by reading the movies. The third chapter focuses primarily on the receivers narratives and young people themselves narratives of your condition projected on the screen